PEMBENTUKAN MENTAL SANTRI PUTRI MELALUI MANAJEMEN KEGIATAN MUHADHOROH DI PONDOK PESANTREN BUSTANUL ‘ULUM - Siti Nurul Khayatun (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2021)
Pesantren has a very important role, for students it is a place to gain knowledge and at the same time as a means of Islamic da'wah. The students of the Bustanul Ulum Islamic Boarding School are equipped with the ability and skills to preach through muhadhoroh activities. The purpose of this study 1) to determine the management of muhadhoroh activities at the Putri Bustanul Ulum Islamic Boarding School, 2) to determine the mental formation of students through muhadhoroh, 3) to determine the implications of muhadhoroh activities in shaping the mentality of students; This research method uses a descriptive qualitative approach and type, data collection techniques used are interviews, documentation, observation and data analysis techniques using steps; data reduction, data presentation, and conclusion drawing. The results of this study are the management of muhadhoroh activities in the mental formation of students starting with planning by providing muhadhoroh training, organizing is carried out by dividing muhadhoroh officers per class, the implementation is carried out starting from the opening, reading the holy verses of the Qur'an, greetings, prayers, core (muhadhoroh), prayer. a and closing, supervision is carried out by the management, and evaluation of the results of the implementation of muhadhoroh; The mental formation of students through muhadhoroh activities there are supporting factors and inhibiting factors, including the obligation and the guidance from all administrators, the inhibiting factors are pessimism and shame in the students' personality.